An Approach to the Study of Organizational Culture Educational Centers - Sarasola, Marcos R. (Education Policy Analysis Archives, 2004)
The main goal of this research is to approach to the school’s culture and subcultures knowledge. Teachers, as learning communities’ members, should be conscious of their basic assumptions in order to accomplish effective change. Culture, as a socio-critical metaphor, includes organizational clime and goes over artefacts and values. It refers to the organizational deeper level of the unconscious assumptions constructed and shared by it members. The quantitative research uses two instruments. A cultural model including six elements (Teacher Efficacy, Teachers as Learners, Collegiality, Mutual Empowerment/Collaboration, Shared visions/School-wide Planning and Transformational Leadership) and proposes that the prevailing culture is the result of the level of development of each individual element. It assumes that in different cultures or at different times in the same culture, there would be a variation in these levels of development. The second scale help to reach two organisational constructs: ‘Transformational leadership culture’ and ‘Transactional leadership culture’. This phase of the investigation centred upon the development and administration of a survey instrument in twenty-five schools and almost eight hundred teachers. That phase of the study is followed by case studies of two schools in which there is a combination of quantitative and qualitative research strategies. Finally, main guidelines are featuring in order to orientate change and innovation for both schools.